Generalized Holographic Principle, Gauge Invariance and the Emergence of Gravity à la Wilczek - Addazi, Andrea; Chen, Pisin; Fabrocini, Filippo; Fields, Chris; Greco, Enrico; Lulli, Matteo; Marcianò, Antonino; Pasechnik, Roman (Frontiers in Astronomy and Space Sciences, 2021)
We show that a generalized version of the holographic principle can be derived from the Hamiltonian description of information flow within a quantum system that maintains a separable state. We then show that this generalized holographic principle entails a general principle of gauge invariance. When this is realized in an ambient Lorentzian space-time, gauge invariance un- der the Poincare' group is immediately achieved. We apply this pathway to retrieve the action of gravity. The latter is cast a la Wilczek through a similar formulation derived by MacDowell and Mansouri, which involves the representation theory of the Lie groups SO(3, 2) and SO(4, 1).